2006
DOI: 10.1210/me.2006-0012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Administration of Estradiol Decreases Expression of Hepatic Lipogenic Genes and Improves Insulin Sensitivity in ob/ob Mice: A Possible Mechanism Is through Direct Regulation of Signal Transducer and Activator of Transcription 3

Abstract: In this study, we used ob/ob mice as a model to investigate the effects of long-term estradiol administration on insulin sensitivity and to explore the mechanisms that underlie the antidiabetic effects of estrogen on mouse liver. Female ob/ob mice were randomly divided into two groups and given estradiol (100 microg/kg.d) or vehicle alone for 4 wk. Estrogen administration improved glucose tolerance and insulin response to glucose in ob/ob mice. Moreover, insulin resistance and liver triglyceride levels were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
110
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(124 citation statements)
references
References 30 publications
14
110
0
Order By: Relevance
“…The microarray analysis successfully identified 47 and 51 genes upand down-regulated by estradiol treatment (Ն2.0-fold, P Ͻ 0.05), and those showing Ն2.5-fold change in gene expression are listed in Table 1. Some of these genes were previously reported as estradiol-responsive (Gao et al, 2006), with changes in expression of 7.1-fold (P Ͻ 0.05) and 9.0-fold (P Ͻ 0.05), respectively, as confirmed by quantitative PCR analysis, suggesting, in part, that our microarray analysis was successful.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The microarray analysis successfully identified 47 and 51 genes upand down-regulated by estradiol treatment (Ն2.0-fold, P Ͻ 0.05), and those showing Ն2.5-fold change in gene expression are listed in Table 1. Some of these genes were previously reported as estradiol-responsive (Gao et al, 2006), with changes in expression of 7.1-fold (P Ͻ 0.05) and 9.0-fold (P Ͻ 0.05), respectively, as confirmed by quantitative PCR analysis, suggesting, in part, that our microarray analysis was successful.…”
Section: Resultssupporting
confidence: 72%
“…In mouse liver, microarray analysis revealed that expression of numerous genes is regulated by ethynyl estradiol, including oxidative metabolism and stress, and lipid metabolism and transport genes (Boverhof et al, 2004). Another study also showed that many mouse hepatic genes were regulated by estradiol, including the genes of lipid metabolism and synthesis, such as leptin receptor (LEPR) and stearoyl-CoA desaturase (SCD) (Gao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that E2 suppresses lipogenesis in white adipose tissue and liver in vivo (32,33). However, it is unknown whether the antilipogenic effects of E2 are mediated via activation of adipocyte or hepatocyte ERs or via the central nervous system, similar to leptin signals from the mediobasal hypothalamus that trigger sympathetic outflow to white adipose tissue (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, an emerging importance of ESR1 in metabolic systems is evident, as a number of ESR1 polymorphisms have been associated with metabolic syndromes like atherosclerosis and type II diabetes (19,29,37,58). Moreover, in hepatic tissue, administration of estradiol downregulates expression of lipogenic genes and improves insulin sensitivity (30). ESR1 was 2.4-fold upregulated with CR (q ϭ 0.03, P ϭ 0.01) and had the highest number of DE target genes compared with any other TF in the four categories of genes in our study (Fig.…”
Section: Esr1 Targets Cr-induced De Genes In Cell Cycle and Apoptoticmentioning
confidence: 99%